2021
DOI: 10.3390/jcm10163638
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Cardiac Troponin and Risk Assessment in Pediatric Supraventricular Tachycardia

Abstract: Cardiac troponin I (cTnI) elevation is common in an acute episode of supraventricular tachycardia (SVT). However, there is limited evidence regarding the prognostic value of cTnI and the predictors of SVT recurrence in pediatric patients. We screened the electronic medical records of all pediatric patients presenting to the emergency departments at five Taiwanese hospitals from 1 January 2010 to 31 May 2021. Our primary outcomes were the occurrence of major adverse cardiac events (MACEs) during the follow-up p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…Research suggests that troponin alone lacks high specificity for diagnosing heart disease. For instance, Yen et al 33 34 found that children with supraventricular tachycardia (SVT) who tested positive for troponin I exhibited clinical symptoms similar to those with normal troponin I levels. Consequently, their findings highlight the limited predictive value of troponin I for SVT recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that troponin alone lacks high specificity for diagnosing heart disease. For instance, Yen et al 33 34 found that children with supraventricular tachycardia (SVT) who tested positive for troponin I exhibited clinical symptoms similar to those with normal troponin I levels. Consequently, their findings highlight the limited predictive value of troponin I for SVT recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding paediatric patients, supraventricular tachycardias represent an important cardiac cause for ED presentation, but in this setting, hs-cTn possesses a low predictive value for the outcomes [ 59 ]. On the other hand, as the incidence of neoplastic pathology is increasing in children, chemotherapy-induced cardiotoxicity became an important health problem.…”
Section: Cardiac Troponins: From Promising To Gold Standardmentioning
confidence: 99%
“…[8] Routine troponin exam in PSVT patients with low risk for coronary artery disease may lead to prolonged length of ED stay, unnecessary exam, and hospitalization. [8][9][10][11][12] However, 1 retrospective study showed elevated troponin I level appear to be associated with adverse outcomes in SVT patients with a history of CAD. [13] This produces doubts as to the prognostic significance of troponin in patients with a huge burden of cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%